Risk Factors Associated With Intradialytic Hypotension in Patients of End Stage Renal Disease on Maintenance Haemodialysis - MUHAMMAD AKRAM BAJWA, TAHIR SHAFI, ABAD-UR-REHMAN AWAN, AIZAZ MAND AHMED (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Intradialytic hypotension is one of the most common complications to be observed during hemodialysis, occurring in about 15-20% of all sessions. The risk factors like interdialytic weight gain, UF rate, net ultrafiltration, pyrexia, food intake, cardiac events dialyzer type etc have been controlled due to modern hemodialysis equipments like hemodialysis machines with their better volumetric controls, sodium profiling, temperature control and patient counseling but still intradialytic hypotension is a major dialysis related complication. Objectives: Identify the risk factors responsible for intradialytic hypotension. Subjects and Methods: This cross-sectional study was comprised of one hundred patients of end stage renal disease carried out in the Department of Nephrology, Shaikh Zayed Hospital, Lahroe between 1st January 2010 to 31st March 2010. All adult patients on maintenance hemodialysis were included in this study. The patients on maintenance hemodialysis <3 months duration and vomiting, diarrhea or bleeding episodes pre-hemodialysis were excluded. These dialysis sessions were categorized in two groups (Group I and Group II). Group I included those dialysis sessions in which the patients developed hypotension during dialysis and Group II included those dialysis sessions in which patients did not develop intradialytic hypotension. Following factors were noted like interdialytic weight gain, ultrafiltration rate, dialyzer type, cardiac events, antihypertensive medication, food intake during dialysis, pyrexia. Results: Total 1907 hemodialysis sessions were included there were 103 (5.4%) patients of symptomatic hypotension (Group I) and 1804 (94.6%) patients of no symptomatic hypotension (Group II). The mean weight gain in group I was 2.2±0.7 kg and 2.1±0.9 kg in group II. The mean ultrafiltration rate in group I was 978±636 ml/h and in group II was 636±367ml/h. In group I, 4 (3.8%) and in group II, 20 (1.1%) sessions had cardiac events during dialysis (P= 0.04). Change in mean pulse rate was -2.1±14.1 in group l and -2.4±11.1 in group ll (p=0.8). the Odd ratios for total time of dialysis was 5.50 (3.59 – 8.43), for lowest systolic blood pressure 5.43(3.55 – 8.32), and lowest diastolic blood pressure 4.85(3.14 – 7.48). Conclusions: We found that interdialytic weight gain, net ultrafiltration, ultrafiltration rate and acute cardiac event were responsible factors causing intradialytic hypotension. Autonomic dysfunction was also a contributing factor among symptomatic hypotensive group.